The study of risk factors associated with accidents in industrial factory construction projects in Chonburi province - Suttisaroj, Siripong; Anantakarn, Kritsada (Frontiers in Engineering Innovation Research, 2026)
This study aims to investigate the factors influencing construction accidents and to propose guidelines for mitigating risk factors associated with accidents in industrial construction projects in Chonburi Province. This research adopts a quantitative approach, using a questionnaire as the primary tool for data collection from personnel and construction workers in industrial factories in Chonburi Province. The sample consists of 132 respondents, including project managers (site engineers), foremen, carpenters, welders, masons, backhoe operators, and general laborers. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results indicate that safety management factors have the highest influence on construction accidents (Mean = 4.10). Other contributing factors, ranked in descending order, include safety behavior in construction work, the use of surveillance technology such as closed-circuit television (CCTV) for accident prevention (Mean = 3.71), deficiencies in tools, equipment, and machinery (Mean = 3.40), and workplace environmental conditions (Mean = 3.01). The lowest-ranked factor is deficiencies in construction design and specifications (Mean = 3.00), based on the perceptions of industrial construction workers. The findings of this study contribute to the clear identification of key risk factors associated with construction accidents and can be utilized to develop effective accident prevention measures and safety management guidelines.